2017
DOI: 10.1016/j.ejbas.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

PCR-detected fungal infection is associated with fatal outcomes in cirrhotic patients with spontaneous peritonitis

Abstract: Background & aims: The rate of mortality from Spontaneous Peritonitis (SP) in cirrhotic patients is still high despite the development of new antibiotic treatments and intensive hospital care. The coexistence of spontaneous fungal peritonitis (SFP) is almost entirely ignored health problem, because it is difficult to be diagnosed at an early stage by conventional culture-based methods. Therefore, this study was designed to employ PCR-based method in evaluating the prevalence of fungal infection in cirrhotic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…[ 154 ]. Polymicrobial infections, i.e., bacterial co-colonization, occurs in 32%-74% of SFP cases[ 148 , 149 , 153 , 154 , 156 ], but early diagnosis by conventional microbial culture is difficult because of the time required for growth[ 155 ], and the efficacy of PCR or assay of the fungal biomarker 1,3-beta- D -glucan in ascitic fluid has not been established[ 149 , 155 ].…”
Section: Spontaneous Fungal Peritonitismentioning
confidence: 99%
See 2 more Smart Citations
“…[ 154 ]. Polymicrobial infections, i.e., bacterial co-colonization, occurs in 32%-74% of SFP cases[ 148 , 149 , 153 , 154 , 156 ], but early diagnosis by conventional microbial culture is difficult because of the time required for growth[ 155 ], and the efficacy of PCR or assay of the fungal biomarker 1,3-beta- D -glucan in ascitic fluid has not been established[ 149 , 155 ].…”
Section: Spontaneous Fungal Peritonitismentioning
confidence: 99%
“…Risk factors associated with hospital mortality in SFP include severe underlying liver disease[ 148 ], Child-Pugh score[ 155 ], MELD score[ 149 ], antibacterial prophylaxis[ 6 ], incidence of HRS[ 6 ], low ascites protein concentration[ 6 ], Acute Physiology And Chronic Health Evaluation II score[ 149 ], and sepsis shock[ 153 ]. SFP mortality is estimated to be 56%-90%[ 5 , 148 , 149 , 151 , 153 ], and 1-mo mortality may[ 148 , 153 ] or may not be significantly higher than SBP mortality[ 149 , 157 ].…”
Section: Spontaneous Fungal Peritonitismentioning
confidence: 99%
See 1 more Smart Citation
“…Early diagnosis of SFP and fungiascites is challenging, partly because of the time required for diagnostic fungal cultures [14] and partly because of lack of suspicion of SFP or fungiascites by the clinician. Diagnostic methods for SFP or fungiascites include polymerase chain reaction (PCR), 1,3-beta-D-glucan assay and galactomannan of the ascitic fluid [9,[14][15][16][17][18].…”
Section: Diagnosis Of Sfp and Fungiascitesmentioning
confidence: 99%
“…Although the clinical characteristics and prognosis of SBP have been well documented [5], the clinical characteristics of SFP and fungiascites in patients with LC are less well known. However, some clinical studies of SFP and fungiascites have been reported in recent years, including those that have evaluated and compared SFP and SBP [6][7][8][9][10] or spontaneous peritonitis with a funguspositive ascitic culture (SFP or fungiascites) and spontaneous peritonitis with a bacteria-positive ascitic culture (culture-positive SBP or bacterascites) [11,12]. In the present article, we review and summarize spontaneous peritonitis due to fungal infections (SFP and fungiascites).…”
Section: Introductionmentioning
confidence: 99%